Polycyclic olefin polymers and anion exchange membranes derived therefrom.
Patent Information
- Application Number
- JP2023505907
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-30
- Filing Date
- 2021-07-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-07-30
AI Technical Summary
【0017】 本明細書に記載の式(I)および式(II)の単量体に由来するランダム共重合体は、これまで得られなかった性質を有するアニオン交換膜を形成することが明らかになった。より具体的には、繰り返し単位を含有するビニル添加共重合体は、式(I)の単量体および式(II)の単量体に由来し、ここでXは、式NR5R6R7+OH-の四級化アンモニウム部分(moiety)であり、式(I)の繰り返し単位の一部は、互いに架橋結合して、水分吸収率が低い膜に製造できる重合体を生成する。このように形成された膜は、80℃で最大200mS/cmの高いイオン伝導率を示し、80℃の1M水酸化ナトリウム溶液で最大1,000時間以上長期安定性を示すため、化学的に安定性の高いアニオン交換膜(AEM)として好適である。一部の実施形態において、該当重合体は、本願に記載の式(I)の単量体に由来する単独重合体である。本発明の炭化水素骨格を含む共重合体から形成された膜は、イオン交換容量(IEC)が約3meq/g~約4meq/g以上と非常に高い。したがって、本発明による膜は、AEM燃料電池、電解槽などの電気化学素子を含む様々な用途に有効に用いることができる。
Smart Images

Figure 0007637760000064 
Figure 0007637760000065 
Figure 0007637760000066
Abstract
Description
[Technical field]
[0001] Cross-reference to related applications This application claims the benefit of U.S. Provisional Application No. 63 / 058,738, filed July 30, 2020, which is incorporated herein by reference.
[0002] The present invention relates to a series of polycycloolefin polymers that function as ionomers and are suitable as anion exchange membranes for use in the manufacture of various electrochemical and separation devices. Specifically, the ionomeric polymers used herein are derived from a series of functionalized norbornene monomers. The present invention further relates to the use of an anion-conducting solid polymer electrolyte as an ion-conducting medium between two electrodes, and an intraelectrode ion-conducting medium that acts as an ion conduit between the electroactive material and the electrolyte. The anion-conducting solid polymer electrolyte can also be used as part of a bipolar membrane when paired with a cation-conducting portion. Electrochemical devices made according to the present invention are usefully used as fuel cells, gas separators, redox flow batteries, water electrolyzers to produce hydrogen, and the like. [Background technology]
[0003] Energy conversion devices using solid polymer electrolytes, such as fuel cells and electrolyzers for producing and separating hydrogen from water, are highly desirable options due to factors such as simplicity, thermodynamic efficiency, and solid-state design. See, for example, BCH Steele and A. Heinzel, Nature, 2001, 414, 345. Such devices are scalable and can be used in small to large scale facilities for transportation, remote and distributed power, electricity / hydrogen production, and separation of specific chemicals such as carbon dioxide, oxygen, and hydrogen. More importantly, fuel cells are a clean energy conversion technology that can reduce the use of fossil fuels. More specifically, fuel cells can be used in stationary power plants, portable electronic devices, and transportation. Fuel cells are also environmentally friendly, easy to charge, and have high energy conversion efficiency.
[0004] Such energy conversion / separation elements use a variety of solid polymer electrolytes in membrane form. Polymer electrolyte membranes include proton (or cation) exchange membranes (PEMs) and anion exchange membranes (AEMs). AEMs or PEMs have the advantage of simplifying the fabrication of electrodes with three-phase boundaries, since liquid / gas pressures do not need to be balanced as in liquid electrolyte elements. AEM and PEM materials are combined to form bipolar membranes that are particularly useful for separation elements and some energy conversion elements. There are currently several commercially available fuel cell electric vehicles and stationary generators that use PEM membranes, but the need for platinum-based electrocatalysts and perfluorinated polymer membranes makes them a costly and less attractive option.
[0005] High pH AEMs have faster oxygen reaction rates than acid-conducting PEMs, can use non-precious metal catalysts, and reduce fuel crossover. However, early AEM membranes had the disadvantages of low ionic conductivity and high water uptake while chemical stability decreased at high pH. In recent years, many researchers, such as Arges, have succeeded in increasing the conductivity (e.g., 100ms / cm at 80°C) and chemical stability (1M NaOH at 80°C). See Arges et al., ACS Appl. Energy Mater. 2018, 1, 2991-3012. These remarkable developments have shown that certain structural moieties can help to solve the deficiencies of AEMs.
[0006] Electrolysers, which produce hydrogen from water, are an emerging technology that can increase the economic viability of hydrogen. Electrochemical separation can enrich or deplete gaseous or liquid feed streams with species such as carbon dioxide, oxygen, and hydrogen. AEM-based devices can offer lower cost of ownership than PEM-based devices because anionic environments, especially high pH environments with hydroxide ions as the electroactive ion, favor the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) by introducing non-platinum-based catalysts. See, for example, DR Dekel, Journal of Power Sources, 2018, 375, 158-169.
[0007] Bipolar membranes can be used in fuel cells and electrolysers where it is advantageous to operate one electrode at high pH (AEM side) and the other at low pH (PEM side). Separation elements such as salt splitters can use AEM, PEM and bipolar membranes in various configurations. In this case, high conductivity and chemical stability (ability to operate at high pH on the AEM side) are especially required. See, for example, "Electrodialysis and Water Reuse," A. Bernardes, M. Rodrigues, J. Ferreira Editors, Springer, ISBN 978-3-642-40249-4, NY (2014), and "Analysis of Factors Limiting the Use of Bipolar Membranes: A Simplified Model to Determine Trends," J. Hineste, G. Pourcelly, Y. Lorrain, F. Persin, C. Gavach, Journal of Membrane Science, 112 (1996) 199-208.
[0008] Also, a variety of low-cost monomers can be used to synthesize hydrocarbon-based anion or hydroxide ion conducting polymers that remain stable in alkaline conditions when compared to the perfluorinated polymers required for PEM-based electrochemical devices. See, for example, PA Kohl, et al., Energy & Environmental Science, 2014, 7, 3135-3191. Perfluorinated polymers are expensive and, furthermore, dangerous to manufacture and may pose significant hazards due to monomer reactivity.
[0009] However, many currently available AEMs do not meet the stringent property requirements of an ideal AEM or bipolar membrane, including (i) high anion (e.g., hydroxide) conductivity, (ii) long-term alkaline stability at the operating temperature of the AEM device, (iii) strong mechanical properties to withstand pressure differentials during use and prevent polymer creep under compression, and (iv) excessive moisture uptake control that can impede ion transport in the electrode membrane. See, for example, S. Gottesfeld, et al., Journal of Power Sources, 2018, 375, 170-184.
[0010] It should also be noted that the polymer backbone structure, the location of the cations within the polymer structure, and the properties of the cations determine the conductivity and long-term alkaline stability of the AEM. Polymer backbones containing polysulfone, polyketone, and poly(aryl ether) moieties are not suitable for AEM formation because they are vulnerable to hydroxide attack and polymer backbone degradation. See, for example, Zhang, X., et al., Polym. Chem. 2018, 9, 699-711 (block poly(arylene ether sulfone) copolymers usable as AEMs) and Akiyama, R., et al., Macromolecules 2016, 49, 4480-4489 (copolymers obtained from dimethylaminomethylated monomers).
[0011] Some AEMs reported in the art have a conductivity of 100 mS / cm or more (60°C to 80°C), and some have a conductivity close to 200 mS / cm at 80°C. See, for example, PA Kohl, et al., Journal of Materials Chemistry A, 2016, 4, 16233-16244; L. Zhu, TJ Zimudzi, N. Li, J. Pan, B. Lin and MA Hickner, Polymer Chemistry, 2016, 7, 2464-2475.
[0012] It has been shown that polymer backbones with block copolymer (BCP) structures can form efficient ion-conducting channels and enhance ionic conductivity. See, for example, PA Kohl, et al., J. Electrochem. Soc., 2020, 167, 054501. However, the synthesis of BCP structures is more demanding, expensive, and limited than that of random copolymers, especially on an industrial scale. Summary of the Invention [Problem to be solved by the invention]
[0013] In view of the above, it is expected that there will continue to be a demand for AEMs that not only have high conductivity but also have improved properties such as the mechanical properties and long-term stability mentioned above.
[0014] It is therefore an object of the present invention to provide a series of polycycloolefin polymers suitable for the preparation of AEMs and / or bipolar membranes having improved properties.
[0015] It is yet another object of the present invention to provide methods for making the polymers and AEMs disclosed herein.
[0016] Further objects and scope of applicability of the present invention will be explained more fully in the following detailed description. [Means for solving the problem]
[0017] Random copolymers derived from monomers of formula (I) and formula (II) described herein have been found to form anion exchange membranes with previously unobtainable properties. More specifically, vinyl-added copolymers containing repeating units are derived from monomers of formula (I) and monomers of formula (II), where X is a group of the formula NR5R6R7 + OH -Some of the repeating units of formula (I) are cross-linked to each other to produce a polymer that can be made into a membrane with low water absorption. The membranes thus formed exhibit high ionic conductivity of up to 200 mS / cm at 80° C. and long-term stability of up to 1,000 hours or more in 1 M sodium hydroxide solution at 80° C., making them suitable as chemically stable anion exchange membranes (AEMs). In some embodiments, the polymer is a homopolymer derived from a monomer of formula (I) described herein. Membranes formed from the copolymers containing a hydrocarbon backbone of the present invention have very high ion exchange capacities (IEC) of about 3 meq / g to about 4 meq / g or more. Thus, the membranes according to the present invention can be effectively used in a variety of applications, including electrochemical devices such as AEM fuel cells and electrolyzers. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic diagram of the synthesis of a cross-linked copolymer of the present invention to form an anion exchange membrane (AEM) of the present invention. [Diagram 2] FIG. 2 is a graph of the ionic conductivity at various temperatures of various AEMs made according to the present invention compared to cross-linked block copolymers. [Diagram 3] FIG. 3 shows the conductivity loss over time for an AEM made according to the present invention. [Figure 4] FIG. 4 shows the cell voltage and power proportional to current density in a hydrogen / oxygen fuel cell operating at 80° C. using an AEM made according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] As used herein, the terms have the following meanings:
[0020] The use of the articles "a," "an," and "the" is deemed to include a plurality of referents unless expressly limited to one referent.
[0021] All numbers, values and / or formulas expressing quantities of ingredients, reaction conditions, and the like in this specification and the claims appended hereto reflect uncertainties of the measurements performed to arrive at such numbers, values and / or formulas and, therefore, unless otherwise indicated, are deemed to include the term "about."
[0022] When the present specification discloses a range of numbers, the range is considered continuous and includes the maximum and minimum values of the range, as well as all values between the maximum and minimum values. When a range relates to integer values, it includes all integers between the maximum and minimum values of the range. Furthermore, when multiple ranges are presented for the purpose of describing a feature or characteristic, the multiple ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein encompass all subranges that the range encompasses. For example, when a range of "1 to 10" is presented, the range should be considered to include all subranges between the minimum value of 1 and the maximum value of 10. Examples of subranges between 1 and 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, etc.
[0023] As used herein, "hydrocarbyl" refers to a group containing carbon and hydrogen atoms, including, but not limited to, alkyl, cycloalkyl, aryl, aralkyl, alkaryl, alkenyl, and the like. A "halohydrocarbyl" is a hydroxyl group in which at least one hydrogen has been replaced with a halogen. A "perhalocarbyl" is a hydroxyl group in which all hydrogens have been replaced with halogens.
[0024] As used herein, "alkyl" refers to a saturated, straight or branched chain hydrocarbon substituent containing the specified number of carbon atoms. It includes propyl, butyl, pentyl, and hexyl groups. Specific alkyl groups include methyl, ethyl, n-propyl, isopropyl, and tert-butyl. Derived expressions such as "alkoxy," "thioalkyl," "alkoxyalkyl," "hydroxyalkyl," "alkylcarbonyl," "alkoxycarbonylalkyl," "alkoxycarbonyl," "diphenylalkyl," "phenylalkyl," "phenylcarboxyalkyl," and "phenoxyalkyl" can be interpreted similarly.
[0025] As used herein, "cycloalkyl" includes all known cyclic radical groups. Representative examples of "cycloalkyl" include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, and the like. Derived expressions such as "cycloalkoxy", "cycloalkylalkyl", "cycloalkylaryl", "cycloalkylcarbonyl", and the like are to be construed in the same manner.
[0026] In this specification, "perhaloalkyl" refers to an alkyl group in which all hydrogen atoms in the alkyl group defined above are replaced with halogen atoms selected from fluorine, chlorine, bromine, or iodine. Examples include trifluoromethyl, trichloromethyl, tribromomethyl, triiodomethyl, pentafluoroethyl, pentachloroethyl, pentabromoethyl, pentaiodoethyl, linear or branched heptafluoropropyl, heptachloropropyl, heptabromopropyl, nonafluorobutyl, nonachlorobutyl, undecafluoropentyl, undecachloropentyl, tridecafluorohexyl, tridecachlorohexyl, and the like. Derived expressions such as "perhaloalkoxy" are also interpreted in the same way. Furthermore, some alkyl groups described in this specification, such as "alkyl", may be partially fluorinated. That is, it means that only a portion of the hydrogen atoms in the alkyl group may be replaced with fluorine atoms, and derived expressions are also interpreted in the same way.
[0027] As used herein, "acyl" has the same meaning as "alkanoyl" represented by the structural formula "R-CO-", where R is "alkyl" having a specific number of carbon atoms as defined herein. Furthermore, "alkylcarbonyl" should be considered as synonymous with "acyl" as defined herein. Specifically, "(C1-C4)acyl" refers to formyl, acetyl or ethanoyl, propanoyl, n-butanoyl, etc. Derived expressions such as "acyloxy" and "acyloxyalkyl" are to be interpreted in the same manner.
[0028] As used herein, "aryl" refers to substituted or unsubstituted phenyl or naphthyl. Specific examples of substituted phenyl or naphthyl include o-, p-, m-tolyl, 1,2-, 1,3-, 1,4-xylyl, 1-methylnaphthyl, 2-methylnaphthyl, etc. "Substituted phenyl" or "substituted naphthyl" include permissible substituents as defined herein or known in the art.
[0029] As used herein, "arylalkyl" refers to an aryl as defined above further attached to an alkyl as defined above. Representative examples include benzyl, phenylethyl, 2-phenylpropyl, 1-naphthylmethyl, 2-naphthylmethyl, and the like.
[0030] As used herein, "alkenyl" refers to an acyclic straight or branched hydrocarbon chain having the specified number of carbon atoms and containing at least one carbon-carbon double bond, including ethenyl and straight or branched propenyl, butenyl, pentenyl, and hexenyl groups. "Arylalkenyl" and derived expressions such as 5- or 6-membered "heteroarylalkenyl" are to be construed similarly. Examples of derived expressions include furan-2-ethenyl, phenylethenyl, 4-methoxyphenylethenyl, and the like.
[0031] As used herein, "heteroaryl" refers to all heteroatoms, including the well-known aromatic radicals. Representative 5-membered heteroaryl radicals include furanyl, thienyl, thiophenyl, pyrrolyl, isopyrrolyl, pyrazolyl, imidazolyl, oxazolyl, thiazolyl, isothiazolyl, and the like. Representative 6-membered heteroaryl radicals include pyridinyl, pyridazinyl, pyrimidinyl, pyrazinyl, triazinyl, and the like. Representative bicyclic heteroaryl radicals include benzofuranyl, benzothiophenyl, indolyl, quinolinyl, isoquinolinyl, cinnolyl, benzimidazolyl, indazolyl, pyridofuranyl, pyridothienyl, and the like.
[0032] "Halogen" or "halo" means chlorine or chloro, fluorine or fluoro, bromine or bromo, and iodine or iodo.
[0033] As used herein, "ionomer" refers to an anion-conducting solid polymer electrolyte that functions as the ion-conducting medium between two electrodes and within the electrodes acting as an ion conduit between the electroactive material and the electrolyte.
[0034] In the broadest sense, "substituted" can be construed to include all permissible substituents of organic compounds. In certain embodiments disclosed herein, "substituted" refers to substitution with one or more substituents independently selected from the group consisting of C1-C6 alkyl, C2-C6 alkenyl, C1-C6 perfluoroalkyl, phenyl, hydroxy, -CO2H, ester, amide, C1-C6 alkoxy, C1-C6 thioalkyl, C1-C6 perfluoroalkoxy, -NH2, Cl, Br, I, F, -NH-lower alkyl, and -N(lower alkyl). However, other suitable substituents known to those of skill in the art can also be used in such embodiments.
[0035] As used herein, "derived" means that the polymer repeat units are polymerized (formed) from polycyclic norbornene-type monomers, such as those according to formula (I) and / or (II), in which case the resulting polymer is formed with a 2,3 double bond of the norbornene-type monomer as follows:
[0036] [ka]
[0037] The above polymerizations are generally known in the art as vinyl addition polymerizations which occur in the presence of organometallic compounds such as organopalladium or organonickel compounds, and are described in more detail below.
[0038] Thus, the polymers provided by the practice of the present invention are a) one or more first repeat units of formula (IA) derived from a monomer of formula (I): [ka] (where: [ka] represents the position of bonding with another repeat unit; Y and Y' are the same or different and are each independently selected from the group consisting of -CH2-, -CH2-CH2-, and -O-; m is an integer from 0 to 3; At least one of R1, R2, R3 or R4 is a group represented by the formula RX; Here, R is (C1-C 10 ) alkylene, (C3-C8) cycloalkylene, (C1-C 10 ) alkylene (C3-C8) cycloalkylene, (C1-C 10 )Alkylene (C3-C8)Cycloalkylene (C1-C 10 ) alkylene, (C1-C 10 ) Alkylene (C6-C 10) arylene, and (C1-C 10 ) Alkylene (C6-C 10 )Arylene(C1-C 10 ) alkylene; X is a halogen or a group of formula N(R5)(R6)(R7) + OH - wherein at least one of R5, R6, and R7 is a group represented by (C1-C 10 )AlkyleneN(R 5’ )(R 6’ ), (C3-C8)cycloalkyleneN(R 5’ )(R 6’ ), (C1-C 10 )Alkylene(C3-C8)CycloalkyleneN(R 5’ )(R 6’ ), (C1-C 10 )Alkylene (C3-C8)Cycloalkylene (C1-C 10 )AlkyleneN(R 5’ )(R 6’ ), (C1-C 10 ) Alkylene (C6-C 10 )Arylene N(R 5’ )(R 6’ ), and (C1-C 10 ) Alkylene (C6-C 10 )Arylene(C1-C 10 )AlkyleneN(R 5’ )(R 6’ ) selected from the group consisting of; R 5’ and R 6’ are the same or different and are linear or branched (C1-C 10 ) alkyl, (C3-C8) cycloalkyl, (C1-C 10 ) alkyl(C3-C8) cycloalkyl, and (C1-C 10 )Alkyl(C6-C 10 ) aryl; The remaining R5, R6, and R7 are the same or different and are straight or branched (C1-C 10 ) alkyl, (C3-C8) cycloalkyl, (C1-C 10) alkyl(C3-C8) cycloalkyl, and (C1-C 10 )Alkyl(C6-C 10 ) aryl; The remaining R1, R2, R3, and R4 are each a hydrogen atom, a straight or branched chain (C1-C 10 ) alkyl, (C3-C8) cycloalkyl, (C1-C 10 ) alkyl(C3-C8) cycloalkyl, and (C1-C 10 )Alkyl(C6-C 10 )aryl; b) one or more second repeat units of formula (IIA) derived from a monomer of formula (II): [ka] (where: [ka] represents the position of bonding with another repeat unit; Z and Z' are the same or different and are each independently selected from the group consisting of -CH2-, -CH2-CH2-, and -O-; n is an integer from 0 to 3; R8, R9, R 10 , and R 11 are the same or different and are hydrogen, straight or branched (C1-C 10 ) alkyl, (C3-C8) cycloalkyl, (C1-C 10 ) alkyl(C3-C8) cycloalkyl, and (C1-C 10 )Alkyl(C6-C 10 )aryl), each independently selected from the group consisting of: X is NR5R6R7 + OH -In the case of, the first repeat unit is crosslinked with another first repeat unit on the same or different polymer chain, whereby the polymer has at least 2% available reactive sites between the repeat units and exhibits an ionic conductivity of at least 150 mS / cm at 80°C. It should be noted here that not all crosslinks occur intermolecularly (between two different polymer chains). Some crosslinks may occur intramolecularly (between two crosslinkable sites on the same polymer chain). All such combinations that are statistically possible are considered part of the present invention.
[0039] The polymers of the present invention, where X is a halogen, can be reacted with a multifunctional amino compound, as described below, to form a crosslinked polymer by intramolecular or intermolecular crosslinking. For example, if the multifunctional amino compound is a difunctional amine, two of the repeating units of formula (IA) will be bonded to the bisamine. This can occur within the same polymer chain (intramolecular crosslinking) or between two polymer chains (intermolecular crosslinking).
[0040] In some embodiments, the polymers of the present invention may contain a single or multiple first repeat units of formula (IA) derived from a monomer of formula (I) as described herein. In another embodiment of the present invention, the polymer is a homopolymer containing only one repeat unit of formula (IA) derived from a monomer of formula (I) as described herein. In another embodiment of the present invention, the monomer of formula (II) may be replaced with an unsaturated hydrocarbyl-substituted organic compound polymerizable with the monomer of formula (I), such as, for example, ethylene, butadiene, styrene, etc., as described below.
[0041] The inventors have found that a crosslinked polymer having the properties required for the production of the membrane according to the present invention (described below) can be produced by appropriately combining a monomer of formula (I) and a monomer of formula (II) together.
[0042] Thus, in some embodiments, the polymer according to the present invention comprises: m and n are 0 or 1; Each Y, Y', Z, and Z' is CH2; At least one of R1, R2, R3, and R4 is a group represented by the formula RX, where R is (CH2) a , (CH2) a Cyclohexylene, (CH2) a Cyclohexylene (CH2) a , (CH2) a Phenylene, and (CH2) a Phenylene (CH2) a where a is an integer from 1 to 10; X is bromine or N(R5)(R6)(R7) + OH - wherein at least one of R5, R6, and R7 is (CH2) a NR 5’ R 6’ , (CH2) a Cyclohexylene NR 5’ R 6’ , (CH2) a Cyclohexylene (CH2) a NR 5’ R 6’ , (CH2) a Phenylene NR 5’ R 6’ , and (CH2) a Phenylene (CH2) a NR 5’ R 6’ wherein a is an integer from 1 to 10; R 5’ and R 6’ are the same or different and are each independently selected from the group consisting of methyl, ethyl, straight or branched chain propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl; The remaining R5, R6, and R7 are the same or different and are each independently selected from the group consisting of methyl, ethyl, straight or branched propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl; The remaining R1, R2, R3, and R4 are each independently selected from the group consisting of hydrogen, methyl, ethyl, straight or branched propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl; R8, R9, R 10 , and R 11 are polymers each independently selected from the group consisting of hydrogen, methyl, ethyl, straight or branched chain propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl.
[0043] In another embodiment, the polymer according to the present invention is + OH - includes polymers in which a first repeat unit crosslinks with another first repeat unit or a second repeat unit, such that between 2% and 10% of the repeat units are crosslinked. In other embodiments, the crosslinks are 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more. In some embodiments, the crosslinks can be greater than 10% or 20% or more depending on the desired properties.
[0044] In another embodiment, the polymer according to the present invention is + OH - In the case of, the polymer includes a first repeat unit that is cross-linked with another first repeat unit or a second repeat unit, whereby cross-linking occurs in at least 5% of the repeat units.
[0045] In another embodiment, the polymer according to the present invention exhibits an ionic conductivity of about 160 mS / cm to about 200 mS / cm at a temperature of about 30°C to about 100°C.
[0046] Generally, the polymers according to the present invention are random copolymers comprising a first repeat unit of formula (IA) derived from a monomer of formula (I) and a second repeat unit of formula (IIA) derived from a monomer of formula (II). However, as previously mentioned, the polymers of the present invention may also be homopolymers containing only one first repeat unit of formula (IA) derived from a monomer of formula (I) as described herein.
[0047] It should be noted that the monomers of formula (I) and (II) generally contain hydrocarbyl side groups, except where the monomer of formula (I) contains hydrocarbyl groups substituted with halogen atoms such as bromine as described herein. The hydrocarbyl side groups impart hydrophobic regions to the overall polymer backbone, making it suitable for producing the membranes of the present invention. Thus, any olefin monomer that imparts said hydrophobic regions can be used as the olefin monomer to form the polymers of the present invention. In some embodiments, the olefin monomers are various well-known hydrocarbyl-substituted olefins, such as, for example, styrene and substituted styrene monomers. In such aspects of the present invention, the polymers may further comprise said hydrocarbyl olefin monomers along with one or more monomers of formula (I) and / or (II). In some embodiments, the polymers of the present invention contain at least one repeat unit of formula (IA) derived from a monomer of formula (I) and at least one suitable styrene monomer. The polymers formed thereby can be crosslinked using the bromo (or halo) functional groups contained in the repeat unit of formula (IA).
[0048] The various monomers of formula (I) and (II) described herein are either already known in the literature or can be prepared by any method known in the art for preparing the same or similar monomers. See, for example, U.S. Patent Nos. 6,825,307 and 9,468,890, which are incorporated herein by reference. Similarly, the polymers of the present invention can be prepared by any method known in the art. See, for example, U.S. Patent Nos. 5,929,181, 6,455,650, 6,825,307, and 7,101,654, which are incorporated herein by reference, for the polymerization of various norbornene-type monomers. In general, suitable methods for preparing the polymers of the present invention include vinyl addition polymerization using organometallic compounds as catalysts, such as organopalladium and organonickel compounds.
[0049] As described above, the film-forming polymer of the present invention is a copolymer containing at least one monomer of formula (I) and one monomer of formula (II). As long as the desired effect is obtained, there is no particular limitation on the molar ratio of the monomers represented by formula (I) or (II) in the production of the polymer of the present invention. In other words, in one embodiment of the present invention, the molar ratio of the first repeating unit to the second repeating unit is generally in the range of about 1:99 to about 99:1. In another embodiment, the molar ratio of the first repeating unit to the second repeating unit is in the range of about 20:80 to about 80:20. In another embodiment, the molar ratio of the first repeating unit to the second repeating unit is in the range of about 40:60 to about 60:40. In another embodiment, the molar ratio of the first repeating unit to the second repeating unit is in the range of about 45:55 to about 55:45. In another embodiment, the molar ratio of the first repeating unit to the second repeating unit is about 50:50.
[0050] The polymer of the present invention may contain two or more kinds of monomers. Therefore, in some embodiments, the polymer of the present invention is a terpolymer. In other words, it contains three kinds of monomer repeat units described in this specification, that is, three kinds of repeat units derived from the monomers of formula (I) and (II). In this case, it may be two different monomers represented by formula (I) and one monomer of formula (II), or it may be two different monomers represented by formula (II) and one monomer of formula (I). There is no particular limit to the molar ratio of the three kinds of monomers forming the terpolymer. For example, the molar ratio may be in the range of 98:1:1 to 1:98:1 to 1:1:98. In other words, any theoretically possible combination of ratios may be adopted. In some embodiments, the molar ratio may be 5:5:90 to 5:90:5 to 90:5:5, or 10:10:80 to 10:80:10 to 80:10:10.
[0051] In some embodiments, the polymers of the present invention may be produced using three or more distinct monomers represented by formulae (I) and (II). Thus, in some embodiments, the polymers of the present invention may be tetrapolymers or pentapolymers. There is no particular limit to the molar ratio of the monomers, so long as the resulting polymer has the desired properties.
[0052] The polymers of the present invention used for forming the membrane generally have a number average molecular weight (M n In another embodiment, the M of the polymer used to manufacture the anion exchange membrane (AEM) is about 30,000 or more. n In another embodiment, the M of the polymer used to manufacture the AEM is about 40,000 or more. n In another embodiment, the M of the polymer used to manufacture the AEM is about 50,000 or more. n In another embodiment, the M of the polymer used to manufacture the AEM is about 60,000 or more. n In another embodiment, the M of the polymer used to manufacture the AEM is about 70,000 or more. n is about 100,000 or more, or 120,000 or more. nThe higher the M of the polymer, the more suitable it is for use in the supported or unsupported form of the AEM described below. n can be measured by well-known methods such as gel permeation chromatography (GPC) with a suitable detector and calibration standards, e.g., a refractive index detector calibrated with low-dispersity polystyrene standards. The polydispersity index (PDI=Mw / Mn) may then be measured, which is typically in the range of 1.1 to 3. Here, M w is the weight average molecular weight.
[0053] The polymers formed according to the present invention can also be utilized to form ionomers for use in the manufacture of electrodes for use with membranes. The polymers used to form the ionomers have a number average molecular weight (M n ) may be lower, typically about 1,000 or more. However, M n Even if it exceeds 1,000, it can still be used as an ionomer.
[0054] In one embodiment of the present invention, the polymer described herein comprises: [ka] [ka] [ka] The polymer comprises a first repeat unit of formula (IA) derived from a monomer of formula (I) selected from, but not limited to, the group consisting of:
[0055] In another embodiment of the present invention, the polymer of the present invention is [ka] [ka] [ka] [ka] [ka] [ka] and a second repeat unit of formula (IIA) derived from a monomer of formula (II) selected from, but not limited to, the group consisting of:
[0056] The polymer according to the present invention comprises 5-(3-bromopropyl)bicyclo[2.2.1]hept-2-ene (NBPrBr), a polymer formed from norbornene (NB); 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), a polymer formed from norbornene (NB); A polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), norbornene (NB), trimethylamine, and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); Polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-ethylbicyclo[2.2.1]hept-2-ene (EtNB); Polymers formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-propylbicyclo[2.2.1]hept-2-ene (PrNB); A polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-ethylbicyclo[2.2.1]hept-2-ene (EtNB), trimethylamine, and N,N,N,N-tetramethyl-1,6-hexanediamine (TMHDA); 5-(3-bromopropyl)bicyclo[2.2.1]hept-2-ene (NBPrBr), a polymer formed from 5-butylbicyclo[2.2.1]hept-2-ene (BuNB); A polymer formed from 5-(4-bromopropyl)bicyclo[2.2.1]hept-2-ene (NBPrBr), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB), trimethylamine, and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), a polymer formed from 5-butylbicyclo[2.2.1]hept-2-ene (BuNB); Polymers formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB), trimethylamine, and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); Polymers formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-hexylbicyclo[2.2.1]hept-2-ene (HexNB); Polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-hexylbicyclo[2.2.1]hept-2-ene (HexNB), trimethylamine, and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA). The compound is selected from the group consisting of, but not limited to,
[0057] Furthermore, the polymer of the present invention has a glass transition temperature (T g ) is very high, in the range of 250°C to 400°C. The polymers of the present invention containing flexible alkyl side chains have a T g However, by appropriately selecting the monomer and adjusting the copolymer, T g It is possible to increase the temperature to above 300°C. Among the polymers used for film formation after quaternization, T gIt has been found that the melting point is never below 300° C. This provides additional thermal property advantages to the membranes produced according to the invention. Although quaternary ammonium headgroups are known to decompose below 250° C., this is surprisingly not the case for the membranes of the invention containing quaternary ammonium headgroups.
[0058] In another aspect of the invention, there is provided an anion exchange membrane (AEM) comprising the polymer of the invention as described above. All of the embodiments of the polymer according to the invention can be used to form the AEM or ionomer of the invention.
[0059] As mentioned above, AEMs characterized by conductivity and long-term alkaline stability are essential to reduce ohmic resistance losses. Hydroxide conductivity is proportional to ion mobility and ion exchange capacity (IEC). Usually, the IEC of AEMs is maintained at a suitable value to avoid large amounts of water absorption that can lead to membrane swelling and reduced ion mobility. Mobility can be improved by forming efficient ion-conducting channels (block copolymers can be utilized) and preventing excessive water absorption in the membrane. Any attempt to improve the IEC of a membrane inevitably requires solving the problem of water drawn by ions. Excessive water absorption can be accommodated by cross-linking, but often at the expense of ion mobility.
[0060] Phase separation within block copolymers is known to aid in the formation of hydrophobic and hydrophilic regions within the polymer. The quaternary ammonium head groups of the hydrophilic phase are where hydroxide transport occurs. It is clear that carbonate conductivity (versus hydroxide conductivity) plays a key role in AEMs as they absorb carbon dioxide from the surrounding atmosphere. In the case of a fuel cell, carbon dioxide at the air cathode is easily absorbed and converts the hydroxides produced at the cathode to bicarbonate or carbonate. When the bicarbonate or carbonate is transported to the hydrogen anode of the fuel cell, the released carbon dioxide is accumulated in the recycled hydrogen fuel along with the water produced at the anode. The carbon dioxide and water are diffused again through the membrane, repeating the hydroxide neutralization and carbonate transport process. Fuel cell tests using freshly supplied hydrogen do not face two important problems: carbon dioxide accumulation and carbonate conduction. Therefore, for efficient carbonate conduction, the IEC and ion mobility need to be as high as possible. The carbonate mobility is much lower than the hydroxide mobility.
[0061] Additionally, AEM fuel cells can operate in high pH environments by utilizing two electrodes: a negative electrode (also known as an anode) where hydrogen is oxidized and a positive electrode (also known as a cathode) where oxygen is reduced: Positive electrode: 2H2O+O2+4e - →4OH - Negative electrode: 4OH - +2H2→4H2O+4e - Forward reaction: O2 + 2H2 → 2H2O (+ energy generation)
[0062] In a fuel cell, oxygen or air is supplied to the oxygen reduction reaction (ORR) cathode and hydrogen gas is supplied to the hydrogen oxidation reaction (HOR) anode. Electrons pass through an external circuit to add useful electrical work. Such reactions are known to be sensitive to the relative humidity of the fuel and oxidant as well as the moisture absorption of the AEM and ionomer. Proper management of moisture in the membrane and electrodes can increase power density. Some of the water electrochemically produced at the HOR electrode is consumed at the cathode by the ORR in AEM fuel cells. Water is transported from the cathode to the anode by electro-osmotic drag accompanied by anion transport. Water also diffuses back from the anode to the cathode. Without the proper amount of moisture in the membrane and electrodes, ionic conductivity decreases and polymer degradation accelerates due to the high reactivity of hydroxides at low moisture concentrations. On the other hand, too much water can easily accumulate in the catalyst layer and prevent efficient flow of ions in the electrodes and membrane. Higher internal stresses and swelling occur within the AEM, which can also lead to mechanical degradation of the membrane.
[0063] Water electrolysis, which produces hydrogen gas and oxygen gas, corresponds to the reverse reaction of a fuel cell, as shown below. Positive electrode: 4OH - →H2O+O2+4e - Negative electrode: 4H2O+4e - →4OH - +2H2 Forward reaction: 2H2O → O2 + 2H2 (energy addition)
[0064] In this case, liquid water is supplied to the cathode (OER) where the oxygen evolution reaction takes place, and hydrogen gas is produced at the anode (HER). It is most preferable to restrict the flow of hydrogen produced at the HER to increase the pressure, so that there is no need to pressurize the hydrogen in a downstream process. Therefore, the membrane must withstand a significant pressure difference.
[0065] Similar electrochemical reactions can be applied to separate specific species from gas or liquid feed streams, and the ORR and OER reactions can be used to produce oxygen pumps. Positive electrode: 4OH -→2H2O+O2+4e - Negative electrode: 2H2O+O2+4e - →4OH - Forward reaction: O2 at the negative electrode moves to O2 at the positive electrode
[0066] Carbon dioxide can be separated from an incoming gas stream in a similar reaction by causing hydroxide ions to react with carbon dioxide to form carbonate. Negative electrode: 2H2O+O2+4e - →4OH - 4OH - +2CO2→2CO3 2- +2H2O Positive electrode: 2CO3 2- →2CO2+O2+4e - Forward reaction: CO2 at the negative electrode moves to CO2 at the positive electrode
[0067] HER and HOR can be applied in the same manner to pump hydrogen from one gas stream to another. Positive electrode: 4OH - +2H2→4H2O+4e - Negative electrode: 4H2O+4e - →4OH - +2H2 Forward reaction: H2 at the positive electrode moves to H2 at the negative electrode
[0068] In each reaction, anions migrate between the two electrodes. To obtain high conductivity, efficient ion channels are required in the AEMs, since the number of ions cannot increase independently due to excessive water absorption (leading to a higher ion exchange capacity (IEC)). It was found that phase separation with block copolymers (BCPs) allows the formation of ion channels with high mobility. The nanochannels were made by nanophase separation between the hydrophobic and hydrophilic blocks of BCP. It should be noted that the BCP morphology does not necessarily lead to high conductivity, since the channels must be interconnected for efficient ion conduction.
[0069] The nature of the polymer backbone and the type / location of hydrophilic groups within the polymer are important for maintaining long-term AEM stability in high pH environments. Experiments have revealed that polar moieties such as ether, ketone, or ester bonds within the polymer or side groups are vulnerable to nucleophilic attack and backbone degradation. Placing cationic head groups at the ends of pendant alkyl tethers is also an effective strategy to mitigate polymer degradation. Among various conductive groups, quaternary ammonium head groups, especially the trimethylammonium cation, offer a good balance between conductivity and stability.
[0070] In addition to the membrane, an ion-conducting polymer is needed to form the electrodes. The electrodes are three-dimensional structures with a very large surface area. In a typical method, an electroactive catalyst is mixed with several anion-conducting polymers to form an ink. The ink is sprayed onto a gas diffusion layer (GDL), which also acts as a current collector. Two electrodes, with the same composition or different catalysts, are pressed onto a solid polymer membrane to create a membrane electrode assembly (MEA). The MEA is placed between solid blocks that distribute the gas or liquid required for the reaction.
[0071] High anion conductivity is important for electrochemical devices that use anion conducting membranes. When a current is passed through the external circuit of the electrochemical device, the ionic current must pass through the ionic membrane between the two electrodes to maintain charge balance within the device. The voltage drop across the ion conducting membrane can be determined by Ohm's law, i.e., multiplying the ionic current by the ionic resistance of the membrane. In energy generating devices such as fuel cells, the output voltage corresponds to the voltage difference between the two electrodes minus the voltage drop across the membrane. Devices that are powered by an external power source, such as electrochemical separators, require an additional voltage drop across the membrane in addition to the voltage difference between the electrodes. Therefore, maximizing the ionic conductivity of the membrane is important for electrochemical devices.
[0072] The membrane conductivity is determined by multiplying the number of mobile ionic charge carriers in the membrane by the mobility of the charge carriers. The concentration of ionic charge carriers can be expressed in equivalents of charge (i.e., moles of charge) per unit mass of polymer. In other words, it corresponds to the ion exchange capacity (IEC) measured in equivalents per gram (eq / g). In practice, it has been found that the water absorption rate in the polymer limits the IEC. High water absorption reduces ion mobility and causes excessive membrane swelling that distorts other properties of the device. Ion mobility depends on various factors, including the distortion of ion paths in the polymer. For example, according to Mandal et al. ACS Appl. Energy Mater. (2019), poly(norbornene) block copolymers form ion paths with high mobility. The hydrophobicity of the poly(norbornene) backbone mitigates water absorption. Block copolymers are known to bind themselves to hydrophilic and hydrophobic regions. With poly(norbornene) block copolymers, a high conductivity of 212 mS / cm at 80 °C can be achieved. A low level of cross-linking was also utilized to mitigate the issue of excessive water absorption, thus allowing the block copolymers to be used to form highly conductive and efficient ionic pathways.
[0073] One of the remaining challenges in designing a stable and conductive AEM is water absorption. Excessive water absorption occurs at high IEC and can cause channel flooding and membrane swelling, leading to mechanical distortion and softening of the membrane. Materials with high IEC tend to absorb water excessively. A small amount of water is necessary to form an ion-solvent shell and dilute the hydroxide salts in the membrane. While the absorbed water must be suitable for ion solvation, excess free water is not productive or desirable. Thus, water content can be divided into bound water (to form the solvent shell) and free water. To maximize ion mobility (i.e., conductivity) while maintaining the mechanical properties of the AEM, an IEC that can balance free and bound water in the membrane should be selected.
[0074] For example, Chen et al., RSC Adv. 2015, 5, 63215-63225, reported that AEMs made with vinyl-doped poly(norbornene) produced very low conductivity (4 mS / cm at 80°C) and showed a slow decrease in conductivity when deposited in 6 M NaOH at room temperature. The AEMs also had low ion exchange capacity. The polymers were not block polymers, and the head group tethers contained ether linkages that are known to be vulnerable to hydroxide attack.
[0075] The inventors have determined that cross-linking repeat units of a polymer backbone imparts unique properties to membranes produced therefrom. Accordingly, this aspect of the invention is a method of forming a membrane, comprising:
[0076] a) As mentioned above casting a film of a polymer, where X is bromine; b) reacting the film with NR5R6R7 in the presence of a base, where at least one of R5, R6, and R7 is (C1-C 10 )AlkyleneN(R 5’ )(R) 6’ ), (C3-C8)cycloalkyleneN(R 5’ )(R 6’ ), (C1-C 10 )Alkylene(C3-C8)CycloalkyleneN(R 5’ )(R 6’ ), (C1-C 10 )Alkylene (C3-C8)Cycloalkylene (C1-C 10 )AlkyleneN(R 5’ )(R 6’ ), (C1-C 10 ) Alkylene (C6-C 10 )Arylene N(R 5’ )(R 6’ ),(C1-C 10 ) Alkylene (C6-C 10 )Arylene(C1-C 10 )AlkyleneN(R 5’ )(R 6’ ) selected from the group consisting of; R 5’ and R 6’are the same or different and are linear or branched (C1-C 10 ) alkyl, (C3-C8) cycloalkyl, (C1-C 10 ) alkyl(C3-C8) cycloalkyl, (C1-C 10 )Alkyl(C6-C 10 )aryl, and the remaining R5, R6, and R7 are the same or different and are linear or branched (C1-C 10 ) alkyl, (C3-C8) cycloalkyl, (C1-C 10 ) alkyl(C3-C8) cycloalkyl, (C1-C 10 )Alkyl(C6-C 10 )aryl; c) The film obtained in b) is reacted with a compound of the formula NR 5’ R 6’ R 7’ with a tertiary amine of 5’ , R 6’ , R 7’ are the same or different and are linear or branched (C1-C 10 ) alkyl, (C3-C8) cycloalkyl, (C1-C 10 ) alkyl(C3-C8) cycloalkyl, (C1-C 10 )Alkyl(C6-C 10 ) are each independently selected from the group consisting of aryl.
[0077] As mentioned above, any of the polymers described herein can be used to make the membranes of the invention. First, the polymer where X is bromine is cast into a suitable film using any method known in the art. Crosslinking of the repeating units can then be accomplished by any method known in the art. In general, the precursor polymer in the form of a film where X is a halogen atom is reacted with a polyfunctional amino compound to form the crosslinked polymer of the invention. Examples of such polyfunctional amino compounds, also referred to as polyamines, contain two or more amino groups and can include various bis-amines, tris-amines, tetra-substituted amines, etc., well known in the art. Examples of bis-amines include bis-aminoalkanes, bis-aminocycloalkanes, bis-amino-aromatic compounds. Similarly, various tris-aminoalkanes, tris-aminocycloalkanes, tris-amino-aromatic compounds, tetra-substituted aminoalkanes, tetra-substituted aminocycloalkanes, tetra-substituted aminoaromatic compounds, etc. can be used.
[0078] Representative examples of bis-amino compounds include, but are not limited to, the following: N,N,N',N'-Tetramethyl-1,2-ethanediamine (TMEDA); N,N,N',N'-Tetraethyl-1,2-ethanediamine (TEEDA); N,N,N',N'-Tetramethyl-1,3-propanediamine (TMPDA); N,N,N',N'-Tetraethyl-1,3-propanediamine (TEPDA); N,N,N',N'-Tetramethyl-1,4-butanediamine (TMBDA); N,N,N',N'-Tetramethyl-1,5-pentanediamine (TMPeDA); N,N,N',N'-Tetramethyl-1,6-hexanediamine (TMHDA); N,N,N',N'-Tetraethyl-1,6-hexanediamine (TEHDA); N,N-Dimethyl-N,N''-diethyl-1,6-hexanediamine (DMDEHDA); N,N,N',N'-Tetramethyl-1,8-octanediamine (TMODA); N,N,N',N'-Tetramethyl-1,10-dodecanediamine (TMDDA); 1,4-Bis(N,N'-dimethyl)cyclohexane; 1,4-Bis(N,N'-dimethyl)benzene.
[0079] Representative examples of other polyfunctional amino compounds include, but are not limited to, the following: N 1 ,N 1 ,N 2 ,N 2 ,N 3 ,N 3 -Hexamethylpropane-1,2,3-triamine. N 1 ,N 1 ,N 3 ,N 3 ,N 6 ,N 6 -Hexamethylhexane-1,3,6-triamine. N 1 ,N 1 ,N 4 ,N 4 ,N 8 ,N 8 -Hexamethyloctane-1,4,8-triamine. N 1 ,N 1 ,N 4 ,N 4 ,N 6 ,N 6 ,N 8 ,N 8 -Octameloctane-1,4,6,8-tetraamine. N 1 ,N 1 ,N 3 ,N 3 ,N 5 ,N 5 -Hexamethylcyclohexane-1,3,5-triamine. N 1 ,N 1 ,N 3 ,N 3 ,N 5 ,N5 -Hexamethylbenzene-1,3,5-triamine.
[0080] Any tertiary amine represented by the formula NR5'R6'R7' can be used to fully quaternize the membrane of the present invention. In other words, the halogen head groups of the polymer chain are completely replaced with tertiary amines. Representative examples of various tertiary amines include, but are not limited to, trimethylamine, triethylamine, tri-n-propylamine, tributylamine, etc. Other tertiary amines substituted with appropriate cycloalkyl or phenyl groups may also be used.
[0081] By using one or more crosslinkers containing two or more amino functional groups, the polymers of the present invention can be prepared with various crosslinker concentrations ranging from about 2 mol% to 50 mol%. For example, FIG. 1 shows an example of the preparation of a bifunctional crosslinked polymer using TMHDA. The polymers of the present invention can be formed into suitable 3D objects such as tubular composites, hollow fibers, dense films, flat sheets, or thin film composites, which are commonly used as membrane materials.
[0082] According to the schematic diagram in FIG. 1, the precursor polymer of the present invention, generally in the form of a film, where X is bromine, is reacted with a multifunctional amine, such as TMHDA, to form the crosslinked polymer of the present invention having a preferred amount of crosslinking depending on the intended application. The crosslinking reaction is usually carried out under ambient room temperature conditions in the presence of a suitable solvent and generally an alkaline medium, such as sodium hydroxide. Other bases can also be used. After the crosslinking reaction is complete, the polymer is further treated with a suitable amine to completely replace all the bromine with amino groups. Suitable amines include trimethylamine, triethylamine, etc. Other suitable amines may also be used.
[0083] As shown in the specific examples below, the appropriate amount of cross-linking of the polymer can provide previously unobtainable properties. For example, attempts to make membranes without cross-linking result in membranes that are too delicate to be used as anion exchange membranes. More importantly, membranes formed with non-cross-linked polymers typically have low ion exchange capacities (IEC), which can be less than 3 meq / g. Membranes made according to the present invention have IECs of at least 3 meq / g, and typically in the range of about 3 meq / g to 3.5 meq / g or more. In some embodiments, membranes made according to the present invention can have IECs of up to 4 meq / g or more. Additionally, membranes made according to the present invention have been found to exhibit very high hydroxide conductivities of 200 mS / cm or more at 80° C. In some embodiments, membranes made according to the present invention exhibit hydroxide conductivities in the range of about 100 mS / cm to about 190 mS / cm at 80° C. Thus, in some embodiments, the membranes of the present invention are capable of an IEC of at least 3 meq / g in aqueous alkaline media at temperatures between about 20° C. and about 100° C. for at least 800 hours.
[0084] Another preferred property of the membranes of the present invention is that they exhibit very high chemical stability, especially in alkaline media. Thus, in some embodiments, the membranes of the present invention are stable in aqueous alkaline media at temperatures between about 20° C. and about 100° C. for at least 800 hours. In another embodiment, the membranes of the present invention remain stable in aqueous alkaline media at temperatures of about 80° C. for 1000 hours.
[0085] The membranes of the invention are therefore useful in a variety of applications, including electrochemical devices and the like. Thus, in one aspect of the invention, there is provided an electrochemical device comprising the membrane of the invention. In another embodiment, there is further provided a fuel cell comprising the membrane of the invention.
[0086] The present invention will now be described in more detail in the following examples, which are for illustrative purposes only and are not intended to limit the scope of the invention.
[0087] Example (general) The following abbreviations define the compounds, devices and / or methods used herein to describe some of the embodiments of the present invention.
[0088] NB: norbornene; BuNB: 5-butylbicyclo[2.2.1]hept-2-ene; HexNB: 5-hexylbicyclo[2.2.1]hept-2-ene; NBPrBr: 5-(3-bromopropyl)bicyclo[2.2.1]hept-2-ene; NBBuBr: 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene; Pd343: (Methyl)palladium (tri-tert-butylphosphine) chloride (CH3)Pd( t Bu3P)Cl; Pd359: (Allyl)palladium (triisopropylphosphine) chloride ((η 3 -allyl)Pd( i Pr3P)Cl); (Crotyl)palladium (tri-tert-butylphosphine) chloride ((crotyl)Pd( t Bu3P)Cl); LiFABA: lithium tetrakis(pentafluorophenyl)-borate (2.5Et2O); TMHDA: N,N,N,N-tetramethyl-1,6-hexanediamine; TFT: α,α,α-trifluorotoluene; THF: tetrahydrofuran; EtOAc: ethyl acetate; MeOH: methanol; IPA: Isopropyl alcohol; ICPOES: Inductively Coupled Plasma Atomic Emission Spectroscopy; GPC: gel permeation chromatography; M w :Weight average molecular weight; M n :number average molecular weight; PDI: polydispersity index; NMR: nuclear magnetic resonance spectroscopy; ppm: parts per million; ppb: parts per billion; HPLC: high performance liquid chromatography;
[0089] Example 1 Random copolymer of BuNB / NBBuBr (molar ratio 75:25, GTR75) The catalyst solution was prepared by mixing Pd343 and LiFABA in a 1:1 molar ratio in a nitrogen-filled glove box. A mixture of toluene and TFT was used as the solvent, and the mixture was stirred for 20 minutes to produce the polymerization-active cationic Pd complex. The monomer, BuNB, and NBBuBr were placed together in a round-bottom flask and purified by three freeze-pump-thaw cycles. Toluene was then added to make a 5 wt% solution of the monomer. A separate round-bottom flask was placed with the catalyst solution in toluene and a dropping funnel was attached to the flask. The monomer solution was added dropwise (10 seconds per drop) to the catalyst solution and stirred vigorously. After the addition was complete, the reaction mixture was removed and precipitated into methanol three times. The resulting polymer was dissolved in toluene and stirred over activated charcoal. The solution was passed through an alumina filter to remove palladium residues. The product was precipitated into methanol. The polymer product was dried at 60°C under vacuum.
[0090] Example 2 NBPrBr homopolymer (designated GT100) The procedure of Example 1 was repeated exactly in Example 2, except that only NBPrBr was used as the olefin monomer.
[0091] Comparative Example 1 Tetrablock copolymer [Poly(BuNB-b-NBBuBr-b-BuNB-b-NBBuBr)] GT75 (BuNB:NBBuBr = molar ratio 25:75) The catalyst was made by dissolving Pd343 (26 mg, 0.074 mmol) and LiFABA (65 mg, 0.074 mmol) in 0.5 g TFT and 0.5 g toluene. BuNB (0.28 g, 1.86 mmol) and toluene (6 mL) were added and stirred. The catalyst was added under vigorous stirring. The BuNB polymerization reaction was completed in 10 min as confirmed by GPC. To this, NBBuBr (1.3 g, 5.6 mmol) and toluene (32 mL) were added and stirred for 3 h to add the NBBuBr block to the BuNB block. After NBBuBr was consumed, the product was confirmed by GPC analysis. BuNB (0.28 g, 1.86 mmol) and toluene (6 mL) were added to form the third block and allowed to react for 10 min. Finally, NBBuBr (1.3 g, 5.6 mmol) and toluene (32 mL) were added and stirred for 3 h to form the fourth block in the polymer chain. The reaction product was quenched by precipitation in methanol. The polymer was purified with activated carbon and filtered to remove catalyst residues. The polymer product was precipitated twice in methanol and dried in vacuum at 60°C.
[0092] Example 3 describes a procedure for producing a membrane of the invention using any of the polymers described herein. For example, any of the polymers produced according to Examples 1-2 can be produced from a membrane substantially according to the procedure of Example 3.
[0093] Example 3 Quaternization and film casting of the polymers of Examples 1-2 and Comparative Example 1 The polymers (0.1 g) of Examples 1-2 and Comparative Example 1 were separately placed in 5 mL of chloroform. The in situ crosslinking reaction was carried out by adding the crosslinker to the polymer / solvent mixture when casting the membrane. The reaction was followed after casting. The crosslinker, TMHDA, was added to the solution in various molar ratios, typically 5 mol%, 10 mol%, 15 mol%, and 20 mol relative to the molar amount of brominated monomer (forming the quaternary ammonium head group) in the polymer. The crosslinker concentration is based on the molar % of TMHDA crosslinker added to the polymer. For example, 5 mol% TMHDA means that up to 10% of the available head groups are consumed by the TMHDA crosslinker. That is, up to at least 10% of the bromine atoms of the bromobutyl groups are replaced by TMHDA. Even if all the crosslinker reacts, it can be difficult to assess the ratio of intramolecular to intermolecular crosslinks. The solution was filtered through a 0.45 μm poly(tetrafluoroethylene) (PTFE) membrane syringe filter, and a film was cast and then dried at 60° C. for 24 hours. The film was colorless, transparent, and flexible. The membrane was immersed in a 50 wt % aqueous solution of trimethylamine for further aminated (48 hours at room temperature). The quaternized membrane was washed with deionized water (DI). The membrane was immersed in a 1 M NaOH solution under nitrogen for 24 hours to convert the bromide ions to hydroxide ions.
[0094] Hydroxide conductivity: Membrane conductivity was measured using four-point probe electrochemical impedance spectroscopy on a PAR2273 potentiostat. Membrane conductivity was measured in HPLC grade water under nitrogen atmosphere. Membranes were allowed to sit for 30 min before measurement. In-plane ionic conductivity was calculated using Equation 1:
number
[0095] In Equation 1, σ is the ionic conductivity (S / cm), L is the length between the sensing electrodes (cm), W and T are the width and thickness of the membrane (cm), and R is the measured resistance (ohms). Long-term (>1000 hours) alkaline stability tests were performed by immersing the membrane in 1M NaOH solution at 80 °C in a Teflon-lined Parr reactor. Before each measurement, the membrane was removed from the solution and washed thoroughly with DI water. After each measurement, the membrane was stored in the reactor with freshly prepared NaOH solution. Long-term alkaline stability was evaluated by the change in ionic conductivity. Each data point was measured three times and the average value was reported. The measurement deviation for each data point was <1%. Additionally, the alkaline stability was further analyzed by characterizing the chemical structure with a Nicolet 6700 FT-IR spectrometer.
[0096] Ion exchange capacity (IEC), water absorption rate (WU), number of freezable water molecules (N free ), the number of non-freezable bound molecules (N bound ), hydration number (λ): 1 H NMR was performed on the preaminated samples to determine the IEC of the membrane. Titration was used to show that the quaternization reaction was quantitative. The titration involved converting the relative anion to chloride and then titrating the chloride of the membrane. 1 It was found that the IEC measurements obtained via H NMR (pre-aminated sample) and titration (post-aminated sample) were identical (within experimental error). For example, the polymer of Example 2 (PNB-X 67 -Y 33 The IEC of 1.9 meq / g and 1.92 meq / g were measured by titration and NMR, and the results were very similar, at 1.9 meq / g and 1.92 meq / g, respectively. This indicates that each bromoalkyl group was quantitatively converted to a quaternary ammonium head group. In other words, each available bromoalkyl group reacted with trimethylamine. 1 The IEC data reported here are based on H NMR, as this was more reliable. 1 The water absorption rate of the film was calculated using Equation 2.
number
[0097] In formula 2, M d is the dry mass, M w is the wet mass of the membrane after removing the surface water. The membrane was measured in the OH form at room temperature. The number of water molecules per ionic group (λ) was calculated by Equation 3.
number
[0098] The amount of freezable water per ion pair in the membrane (N free ) and the amount of bound water (N bound ) was calculated by differential scanning calorimetry (DSC). DSC measurements were performed on a Discovery DSC equipped with an autosampler (TA Instruments). The membranes were hydrated and excess water was removed from the surface. 5–10 mg samples were sealed in DSC pans. The samples were cooled to -50 °C and then heated to 30 °C at a rate of 5 °C / min under N2 (20 mL / min). The amount of freezable and unfrozen water was calculated by Equations 4–6.
number
[0099] M free is the mass of water that can be frozen, M tot is the total mass of water present in the membrane. The weight fraction of freezable water was calculated by Eq.
number
[0100] Mw is the wet mass of the membrane, M dは is the dry mass of the membrane. H f is the enthalpy calculated as the integral of the DSC freeze peak, and H ice is the enthalpy of fusion of water corrected for the subzero freezing point using Equation 6.
number
[0101] ΔC p is the difference in specific heat capacity between liquid water and ice. ΔT f refers to freezing point depression.
[0102] Sacrificial X-ray scattering (SAXS): SAXS was used to analyze the phase separation of the block copolymer AEM. Hydrated films of the bromide form were tested in air using the NSLS-II beamline at the Functional Nanomaterials Research Center (Brookhaven National Laboratory, Upton, NY). The wave vector (q) was calculated by Equation 7, where 2q is the scattering angle.
number
[0103] The characteristic separation length or spacing between domains (d) (i.e., the Bragg spacing) was calculated by Eq. 8.
number
[0104] Membranes produced according to Example 3 derived from the polymers of Example 1 and Comparative Example 1 (referred to as GTR75-15 and GT75-15, respectively) were used for electrochemical testing in an alkaline fuel cell (AEMFC). The anode and cathode were fabricated using the slurry method described in Kohl, et al., J. Membr. Sci. 2019, 570-571, 394-402. A low molecular weight form of poly(BuNB-b-NBPrBr-b-BuNB) polymer (20.5 kDa) was used as the ionomer. The ionomer of Vulcan XC-72 catalyst and 50% platinum were ground together in isopropanol. The catalyst / ionomer slurry was then sonicated at room temperature to ensure uniform mixing. The slurry was spray coated onto 1% waterproof Toray TGPH-060 carbon paper and dried at room temperature. The platinum loading was 2.1 mg / cm. 2 and the ionomer to carbon ratio was 40%.
[0105] The electrode membrane assembly was immersed in 1M NaOH for 1.5 hours to exchange bromide for hydroxide. A Fuel Cell Technology Test Station with single pass serpentine graphite plates and PTFE gaskets was used. Each test was performed on a Scribner 850e Fuel Cell Test Station operated at 60 °C using 0.5 L / min of humidified H2 and O2 gas. The dew points of the anode and cathode gas streams were adjusted during the experiment.
[0106] Table 1 summarizes the results of the ionic conductivity measured for the polymers of Examples 1-2 and Comparative Example 1 crosslinked with various mole % of TMHDA.
[0107] [Table 1]
[0108] As is evident from the data shown in Table 1, membranes with the desired ion conduction properties can be produced at temperatures between room temperature and 80°C. That is, by adjusting the crosslinking concentration, it is possible to achieve an IEC of up to 4.55 meq / g and a hydroxide ion conductivity of up to 194 mS / cm at 80°C. Furthermore, according to the data shown in Table 1, the properties of the random polymers and / or homopolymers are similar to those of the block copolymer of Comparative Example 1. Crosslinking higher than 5 mol% appears to reduce the hydroxide ion conductivity. Furthermore, the data summarized in Table 1 show that increasing temperature increases the conductivity of the membrane. This is also shown graphically in Figure 2. For all membranes tested herein, the conductivity increases with increasing temperature within the temperature range of 25°C to 80°C. This phenomenon is due to the more active thermal motion of ions at higher temperatures. A higher level of crosslinking can stabilize the polymer membrane and suppress excessive water expansion, but at the expense of reduced ion mobility. Ion conductivity increased slightly at light crosslinking, with a crosslinker concentration of 5 mol%, but decreased at higher crosslinking levels. For GTR75-5 (5 mol % crosslinker), the hydroxide conductivity was 94 mS / cm and 194 mS / cm at 25 and 80 °C, respectively. GTR75-20 (20 mol % crosslinker) had lower ionic conductivity (61 mS / cm and 132 mS / cm at 25 and 80 °C, respectively). Without crosslinking, the water absorption was too high to produce a stable film with excessive swelling.
[0109] Hydroxide conductivity normalized to IEC (s / IEC) indicates the hydroxide ion mobility of the membrane. It measures the average effect of intramembrane cations contributing to hydroxide conductivity. Because the IEC values for each membrane are nearly the same (the only mass change is due to the added crosslinker), the hydroxide mobility can be tracked with the conductivity. The data in Table 1 show that GT100-15 (polymer of Example 2 with a crosslinker concentration of 15 mol %) showed the highest efficiency, while GTR75-20 (polymer of Example 1 with a crosslinker concentration of 20 mol %) showed the lowest efficiency. Membranes prepared from the random polymer of Example 1 or the homopolymer of Example 2 showed similar properties to the similarly crosslinked block copolymer of Comparative Example 1.
[0110] Table 2 shows the area resistivity (ASR), water absorption value, hydration number, N free and N bound The results of the film testing of the degree of quaternization measured by NMR and the d-spacing measured by SAXS are summarized in the table.
[0111] [Table 2]
[0112] It is important to note that the higher the hydration number, the higher the conductivity of the membrane. Hydration numbers of 10 and above appear to produce membranes with previously unattainable conductivity properties.
[0113] Ionic ASR is another key property that determines the efficiency of membranes in various applications. Ionic ASR was calculated based on polymer conductivity and membrane thickness at 80°C by applying the formula ASR=L / σ, where L is the film thickness and σ is the ionic conductivity. The ASR of the membrane formed from 5 mol % of the crosslinked polymer of Example 2 (GTR75-5) was 0.05 ohm-cm. 2 This is the ARPA-E IONICS (Department of Energy, USA) target of ≦0.04 ohm-cm 2The ionic ASR values for the other membrane samples are summarized in Table 2. Note that the membranes with less than 10% cross-linking are close to the ionic ASR target.
[0114] Water absorption rate (WU), hydration number (λ), number of freezable water molecules (N free ) and the number of unfrozen conjugate molecules (N bound ) was measured for each prepared membrane, and the results are summarized in Table 2. For each polymer, an optimal water absorption rate was found, which is necessary for ion hydration and efficient channel conduction. Too much water in the form of free water can lead to excessive expansion of the ion-conducting channels, membrane softening, and channel flooding, which can lead to poor performance. As shown in Table 2, the WU of the membrane is inversely related to the crosslinker concentration. The best performing membrane, which is 5 mol% of the crosslinked polymer of Example 1 (GTR75-5), has a conductivity of 194 mS / cm at 80°C and a WU of 114%, which is very similar to the membrane made with the block copolymer of Comparative Example 1 (GT75-5 has a conductivity of 201 mS / cm at 80°C and a WU of 119%). With a slightly increased crosslinker concentration of 10 mol% of the crosslinked polymer of Example 1 (GTR75-10), the membrane showed a slightly lower WU (82%) and lower conductivity (171 mS / cm at 80°C). The membrane with the highest crosslinker concentration, 20 mol % crosslinked polymer of Example 1 (GTR75-20), has poor ion mobility, with the lowest WU (64%) and conductivity (132 mS / cm at 80° C.).
[0115] The number of water molecules per ion pair (head group and mobile counter ion) and the hydration number (λ) are determined by the number of bound or unfreezable water (N bound ) and non-binding or freezable (N free ) of water, each of which is determined by DSC freezing point measurements. As shown in Table 2, the hydration numbers of the test samples increased with decreasing crosslinker concentration, similar to WU. Bound water was calculated by subtracting free water from the hydration number. The results for each membrane are shown in Table 2. Each membrane sample had 6-7 bound molecules per ion pair, regardless of conductivity, but the number of free water molecules ranged from 0 to 6.20 per ion pair. The membrane with the highest conductivity (GTR75-5, 194 mS / cm at 80°C) had 100% N per ion pair.free is 8.50, N bound On the other hand, the poorly performing membrane (GTR75-20, 132 mS / cm at 80°C) had a N per ion pair. free is 1.44, N bound was 8.82, which was similar to the values measured for the membranes made with the block copolymers (i.e., GT75-5 and GT75-15 in Comparative Example 1).
[0116] At high crosslinking densities, water molecules, especially free water, have difficulty filling the membrane because it was not as flexible as in tightly crosslinked membranes. For uncrosslinked membranes with less than six free water molecules per ion pair, the conductivity was less than 70 mS / cm. See, for example, Kohl, et al., J. Membr. Sci. 2019, 570-571, 394-402. The low conductivity of GTR75-20 is due to the low free water level. This indicates that some free water is essential for hydration of the channel and high ion mobility. In addition, it was shown that the number of free water decreases with higher crosslinking density, which is likely due to limited connectivity between hydrophilic domains. For samples with different crosslinking densities from each other, it can be seen that the domain distance changes little. Therefore, optimization of the free and bound water molecules of the membrane is necessary to obtain maximum efficiency.
[0117] The alkaline stability of the membrane according to the invention is essential for its use in various applications, as anticipated herein. More specifically, the long-term alkaline resistance of AEM is essential for electrochemical devices operating for thousands of hours, especially at high pH and temperature. Stability measurements were performed by immersing the membrane in a freshly prepared 1M NaOH solution at 80°C for over 1000 hours. Conductivity was measured periodically during the aging process. AEM only lost 1.25% to 1.32% conductivity over the aging period of over 1000 hours, as shown in Figure 3. Each data point in Figure 3 is the average of three separate measurements. The deviation of the individual measurements for each data point was less than 1%. The three measurements showed variation only at the third significant figure. The low conductivity loss values are acceptable for ARPA-E IONICS targets.
[0118] Example 4 illustrates the use of the membrane according to the present invention in fuel cell performance evaluation. A membrane made by the procedure described in Example 3 using the polymer of Example 1 with 15 mol% of crosslinker (designated GTR75-15) was selected for demonstration in an alkaline fuel cell. It is compared with a membrane made from the block copolymer of Comparative Example 1 containing 15 mol% of the same crosslinker (designated GT75-15).
[0119] Example 4 Fuel cell performance testing The membrane was mechanically robust and easily assembled into fuel cell hardware. Fuel cell testing was performed at a typical operating temperature of 80 °C. The fuel cell was first conditioned at a cell voltage of 0.5 V for 1 h, followed by conditioning at 0.2 V for 1 h. The open circuit voltage (OCV) after conditioning was 1.042 V. Current-voltage measurements and impedance spectra were recorded periodically at 0.4 V. The dew points of the gases fed to the anode and cathode were set at 52 °C (74.8% RH) and 56 °C (86.6% RH), respectively.
[0120] Figure 4 shows the 10μm GTR75-15 AEM and H 2 / Current-voltage and current-power density curves for a 10 μm GT75-15 AEM operating with O2 and a feed rate of 1 L / min. The cell temperature was 80°C. The anode / cathode dew points were optimized at 70°C / 74°C for the GTR75-15 and 68°C / 70°C for the GT75-15. The actual anode loading was 0.672 mg. Pt / Ru cm -2 and for the cathode, 0.584 mg without back pressure. Pt / Ru cm -2 The fuel cell results demonstrate that the membrane can be successfully integrated into an electrochemical device.
[0121] Although the present invention has been described by way of example with reference to the above embodiments, the present invention is not limited to the embodiments, but rather encompasses the general scope of the present invention as described above. Various modifications and embodiments can be made without departing from the spirit of the present invention. The matters disclosed in this specification include the following. 〔1〕 a) one or more first repeat units of formula (IA) derived from a monomer of formula (I): [ka] (where: [ka] represents the position of bonding with another repeat unit; Y and Y' are the same or different, and each represents -CH 2 -, -CH 2 -CH 2 -, -O-, and -O-; m is an integer from 0 to 3; R 1 、R 2 、R 3 or R 4 at least one of is a group represented by the formula RX Here, R is (C 1 -C 10 ) alkylene, (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) Alkylene (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) Alkylene (C 3 -C 8 ) Cycloalkylene (C 1 -C 10 ) alkylene, (C 1 -C 10 ) Alkylene (C 6 -C 10 ) arylene, and (C 1 -C 10 ) Alkylene (C 6 -C 10 )Arylene(C 1 -C 10 ) alkylene; X is a halogen or a group of the formula N(R 5 )(R 6 )(R 7 ) + OH - where R 5 、R 6 , and R 7 At least one of (C 1 -C 10 )AlkyleneN(R 5’ )(R 6’ )、(C 3 -C 8 ) Cycloalkylene N(R 5’ )(R 6’ )、(C 1 -C 10 ) Alkylene (C 3 -C 8 ) Cycloalkylene N(R 5’ )(R 6’ )、(C 1 -C 10 ) Alkylene (C 3 -C 8 ) Cycloalkylene (C 1 -C 10 )AlkyleneN(R 5’ )(R 6’ )、(C 1 -C 10 ) Alkylene (C 6 -C 10 )Arylene N(R 5’ )(R 6’ ), and (C 1 -C 10 ) Alkylene (C 6 -C 10 )Arylene(C 1-C10 )AlkyleneN(R 5’ )(R 6’ ) selected from the group consisting of; R 5’ and R 6’ are the same or different and are linear or branched (C 1 -C10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 )Alkyl(C 3 -C 8 ) cycloalkyl, and (C1-C 10 )Alkyl(C 6 -C 10 ) aryl; Remaining R 5 、R 6 , and R 7 are the same or different and are linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 )Alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 )Alkyl(C 6 -C 10 ) aryl; Remaining R 1 、R 2 、R 3 , and R 4 is hydrogen, straight or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 )Alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 )Alkyl(C 6 -C 10 )aryl; b) one or more second repeat units of formula (IIA) derived from a monomer of formula (II):
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
[11] above, having an ion exchange capacity of at least 3 meq / g in an alkaline aqueous medium at a temperature of about 20° C. to about 100° C. for at least 800 hours. 〔14〕 An electrochemical device comprising the film according to
[11] above. 〔15〕 A fuel cell comprising the membrane according to
[11] above. 〔16〕 The membrane described in
[11] above, wherein the polymer is a random copolymer comprising the first repeating unit of formula (IA) derived from a monomer of formula (I) and the second repeating unit of formula (IIA) derived from a monomer of formula (II). 〔17〕 The membrane described in
[11] above, wherein the polymer is a random copolymer comprising the first repeating unit of formula (IA) derived from a monomer of formula (I) and the second repeating unit of formula (IIA) derived from a monomer of formula (II). 〔18〕 The polymer is A polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), norbornene (NB), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); A polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-ethylbicyclo[2.2.1]hept-2-ene (EtNB), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); A polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); A polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr), 5-hexylbicyclo[2.2.1]hept-2-ene (HexNB), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); Polymer formed from 5-(4-bromopropyl)bicyclo[2.2.1]hept-2-ene (NBPrBr), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA). The membrane according to
[11] above, selected from the group consisting of: 〔19〕 a) casting a film of the polymer described in
[11] above, where X is bromine; b) The film was treated with NR 5 R 6 R 7 reacting with, where R 5 、R 6 , and R 7 At least one of (C 1 -C 10 )AlkyleneN(R 5’ )(R 6’ )、(C 3 -C 8 ) Cycloalkylene N(R 5’ )(R 6’ )、(C 1 -C 10 ) Alkylene (C 3 -C 8 ) Cycloalkylene N(R 5’ )(R 6’ )、(C 1 -C 10 ) Alkylene (C 3 -C 8 ) Cycloalkylene (C 1 -C 10 )AlkyleneN(R 5’ )(R 6’ )、(C 1 -C 10 ) Alkylene (C 6 -C 10 )Arylene N(R 5’ )(R 6’ ), and (C 1 -C 10 ) Alkylene (C 6 -C 10 )Arylene(C 1 -C 10 )AlkyleneN(R 5’ )(R 6’ ) selected from the group consisting of; R 5’ and R 6’ are the same or different and are linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 )Alkyl(C 3 -C 8 ) cycloalkyl, and (C 1-C 10 )Alkyl(C 6 -C 10 ) aryl; Remaining R 5 、R 6 , and R 7 are the same or different and are linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 )Alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 )Alkyl(C 6 -C 10 )aryl; c) The film obtained in b) is reacted with a compound of the formula NR 5’ R 6’ R 7’ with a tertiary amine of 5’ 、R 6’ , and R 7’ are the same or different and are linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 )Alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 )Alkyl(C 6 -C 10 ) aryl A method for forming the film according to
[11] above, comprising: 〔20〕 The method according to claim 19, wherein the base is an alkali base.
Claims
1. a) one or more first repeat units of formula (IA) derived from a monomer of formula (I): 【Chemistry 1】 (where: 【Chemistry 2】 represents the position of bonding to another repeat unit; Y and Y' are the same or different and are -CH 2 --, --CH 2 -CH 2 -, -O-, and -O-; m is an integer from 0 to 3; R 1 , R 2 , R 3 and R 4 At least one of the groups is a group represented by the formula R-X, Here, R is (C 1 -C 10 ) alkylene, (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene (C 3 -C 8 ) Cycloalkylene (C 1 -C 10 ) alkylene, (C 1 -C 10 ) alkylene (C 6 -C 10 ) arylene, and (C 1 -C 10 ) alkylene (C 6 -C 10 ) Arylene (C 1 -C 10 ) alkylene; X is a halogen; The remaining R 1 , R 2 , R 3 , and R 4 is hydrogen, linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl); and b) one or more second repeat units of formula (IIA) derived from a monomer of formula (II): 【Chemistry 3】 (where: 【Chemistry 4】 represents the position of bonding to another repeat unit; Z and Z' are the same or different and are -CH 2 --, --CH 2 -CH 2 -, -O-, and -O-; n is an integer from 0 to 3; R 8 , R 9 , R 10 , and R 11 are the same or different and are hydrogen, straight or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; a part of X of the first repeating unit in the random copolymer containing the formula: X of another first repeating unit on the same or different polymer chain is NR 5 R 6 R 7 (wherein at least one of R 5 , R 6 and R 7 is (C 1 -C 10 ) alkylene N(R 5 ' ) (R 6 ' ), (C 3 -C 8 ) cycloalkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene (C 1 -C 10 ) alkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 )alkylene(C 6 -C 10 )aryleneN(R 5 ' )(R 6 ' ), and (C 1 -C 10 )alkylene(C 6 -C 10 )arylene(C 1 -C 10 )alkyleneN(R 5 ' )(R 6 ' ); R 5 ' and R 6 ' are the same or different and are each independently selected from the group consisting of straight or branched (C 1 -C 10 )alkyl, (C 3 -C 8 )cycloalkyl, (C 1 -C 10 )alkyl(C 3 -C 8 )cycloalkyl, and (C 1 -C 10 )alkyl(C 6 -C 10 )aryl; the remaining R 5 , R 6 , and R 7 are the same or different and are each independently selected from the group consisting of linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl. ) thereby having 2% to 15% crosslinks between the first repeat units, and the remaining first repeat units have X replaced with a tertiary amine and have converted halide ions to hydroxide ions, and the crosslinked polymer exhibits an ionic conductivity of at least 150 mS / cm at 80° C.
2. m and n are 0 or 1; Each Y, Y', Z, and Z' is CH 2 and R is (CH 2 ) a , (CH 2 ) a Cyclohexylene, (CH 2 ) a Cyclohexylene (CH 2 ) a , (CH 2 ) a Phenylene, and (CH 2 ) a Phenylene (CH 2 ) a where a is an integer from 1 to 10; Here, R 5 , R 6 , and R 7 At least one of (CH 2 ) a N.R. 5’ R 6’ , (CH 2 ) a Cyclohexylene NR 5’ R 6’ , (CH 2 ) a Cyclohexylene (CH 2 ) a N.R. 5’ R 6’ , (CH 2 ) a Phenylene NR 5’ R 6’ , and (CH 2 ) a Phenylene (CH 2 ) a N.R. 5’ R 6’ where a is an integer from 1 to 10; R 5’ and R 6’ are the same or different and are each independently selected from the group consisting of methyl, ethyl, straight or branched chain propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl; The remaining R 5 , R 6 , and R 7 are the same or different and are each independently selected from the group consisting of methyl, ethyl, straight or branched chain propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl; The remaining R 1 , R 2 , R 3 , and R 4 are each independently selected from the group consisting of hydrogen, methyl, ethyl, straight or branched chain propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl; R 8 , R 9 , R 10 , and R 11 2. The crosslinked polymer of claim 1, wherein each is independently selected from the group consisting of hydrogen, methyl, ethyl, straight or branched propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, methylcyclopentyl, methylcyclohexyl, and benzyl.
3. A cross-linked polymer as described in claim 1, having the cross-linking bonds between 2% or more and 10% or less of the repeating units.
4. a) one or more repeat units of formula (IA) derived from a monomer of formula (I): 【Chemistry 5】 (where: 【Chemistry 6】 represents the position of bonding to another repeat unit; Y and Y' are the same or different and are -CH 2 --, --CH 2 -CH 2 -, -O-, and -O-; m is an integer from 0 to 3; R 1 , R 2 , R 3 and R 4 At least one of the groups is a group represented by the formula R-X, where R is (C 1 -C 10 ) alkylene, (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene (C 3 -C 8 ) Cycloalkylene (C 1 -C 10 ) alkylene, (C 1 -C 10 ) alkylene (C 6 -C 10 ) arylene, and (C 1 -C 10 ) alkylene (C 6 -C 10 ) Arylene (C 1 -C 10 ) alkylene; X is a halogen; The remaining R 1 , R 2 , R 3 , and R 4 is hydrogen, linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; a polymer consisting of (wherein the polymer is a homopolymer or a random copolymer consisting of one or more repeat units of formula (IA)), in which a portion of X in the repeat units of formula (IA) is in a state where X in another repeat unit on the same or a different polymer chain is in a state where NR 5 R 6 R 7 (wherein at least one of R 5 , R 6 and R 7 is (C 1 -C 10 ) alkylene N(R 5 ' ) (R 6 ' ), (C 3 -C 8 ) cycloalkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene (C 1 -C 10 )alkyleneN(R 5 ' )(R 6 ' ), (C 1 -C 10 )alkylene(C 6 -C 10 )aryleneN(R 5 ' )(R 6 ' ), and (C 1 -C 10 )alkylene(C 6 -C 10 )arylene(C 1 -C 10 )alkyleneN(R 5 ' )(R 6 ' ); R 5 ' and R 6 ' are the same or different and are selected from the group consisting of linear or branched (C 1 -C 10 )alkyl, (C 3 -C 8 )cycloalkyl, (C 1 -C 10 )alkyl(C 3 -C 8 )cycloalkyl, and (C 1 -C 10 )alkyl(C 6 -C 10 )aryl; the remaining R 5 , R 6 , and R 7 are the same or different and are each independently selected from the group consisting of straight or branched chain (C 1 -C 10 )alkyl, (C 3 -C 8 )cycloalkyl, (C 1 -C 10 )alkyl(C 3 -C 8 )cycloalkyl, and (C 1 -C 10 )alkyl(C 6 -C 10 )aryl. ) whereby 2% to 15% of the repeat units have crosslinks, and the remaining repeat units of formula (IA) have X replaced with a tertiary amine and have converted halide ions to hydroxide ions, and exhibit an ionic conductivity of at least 150 mS / cm at 80° C.
5. The crosslinked polymer according to claim 4, wherein the polymer consisting of one or more repeat units of formula (IA) derived from the monomer of formula (I) is a homopolymer.
6. An anion exchange membrane comprising the crosslinked polymer according to claim 4.
7. The random copolymer comprising one or more repeat units of formula (IA) derived from a monomer of formula (I) and one or more second repeat units of formula (IIA) derived from a monomer of formula (II) is a random copolymer comprising one first repeat unit of formula (IA) derived from a monomer of formula (I) and one second repeat unit of formula (IIA) derived from a monomer of formula (II). The crosslinked polymer according to claim 1.
8. The second repeat unit of formula (IIA) is 【Chemistry 8-1】 【Chemistry 8-2】 【Chemistry 8-3】 【Chemistry 8-4】 【Chemistry 8-5】 【Chemistry 8-6】 2. The crosslinked polymer of claim 1, which is derived from a monomer of formula (II) selected from the group consisting of:
9. A crosslinked polymer formed from 5-(3-bromopropyl)bicyclo[2.2.1]hept-2-ene (NBPrBr) as the monomer of formula (I), norbornene (NB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), norbornene (NB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7; A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-ethylbicyclo[2.2.1]hept-2-ene (EtNB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-propylbicyclo[2.2.1]hept-2-ene (PrNB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-ethylbicyclo[2.2.1]hept-2-ene (EtNB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; A crosslinked polymer formed from 5-(4-bromopropyl)bicyclo[2.2.1]hept-2-ene (NBPrBr) as the monomer of formula (I), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; and A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-hexylbicyclo[2.2.1]hept-2-ene (HexNB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; The crosslinked polymer of claim 1 selected from the group consisting of:
10. a) one or more first repeat units of formula (IA) derived from a monomer of formula (I); 【Chemistry 9】 (where: 【Chemistry 10】 represents the position of bonding to another repeat unit; Y and Y' are the same or different and are -CH 2 --, --CH 2 -CH 2 -, -O-, and -O-; m is an integer from 0 to 3; R 1 , R 2 , R 3 and R 4 At least one of the groups is a group represented by the formula R-X, Here, R is (C 1 -C 10 ) alkylene, (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene (C 3 -C 8 ) Cycloalkylene (C 1 -C 10 ) alkylene, (C 1 -C 10 ) alkylene (C 6 -C 10 ) arylene, and (C 1 -C 10 ) alkylene (C 6 -C 10 ) Arylene (C 1 -C 10 ) alkylene; X is a halogen; The remaining R 1 , R 2 , R 3 , and R 4 is hydrogen, linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl); and b) one or more second repeat units of formula (IIA) derived from a monomer of formula (II): 【Chemistry 11】 (where: 【Chemistry 12】 represents the position of bonding to another repeat unit; Z and Z' are the same or different and are -CH 2 --, --CH 2 -CH 2 -, -O-, and -O-; n is an integer from 0 to 3; R 8 , R 9 , R 10 , and R 11 are the same or different and are hydrogen, straight or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; a part of X of the first repeating unit in the random copolymer containing the formula: X of another first repeating unit on the same or different polymer chain is NR 5 R 6 R 7 (wherein at least one of R 5 , R 6 and R 7 is (C 1 -C 10 ) alkylene N(R 5 ' ) (R 6 ' ), (C 3 -C 8 ) cycloalkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) cycloalkylene (C 1 -C 10 ) alkylene N(R 5 ' ) (R 6 ' ), (C 1 -C 10 )alkylene(C 6 -C 10 )aryleneN(R 5 ' )(R 6 ' ), and (C 1 -C 10 )alkylene(C 6 -C 10 )arylene(C 1 -C 10 )alkyleneN(R 5 ' )(R 6 ' ); R 5 ' and R 6 ' are the same or different and are each independently selected from the group consisting of straight or branched (C 1 -C 10 )alkyl, (C 3 -C 8 )cycloalkyl, (C 1 -C 10 )alkyl(C 3 -C 8 )cycloalkyl, and (C 1 -C 10 )alkyl(C 6 -C 10 )aryl; the remaining R 5 , R 6 , and R 7 are the same or different and are each independently selected from the group consisting of linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; thereby having crosslinks between 2% to 15 of said first repeat units, and the remaining first repeat units include a crosslinked polymer in which X is replaced with a tertiary amine and halide ions are converted to hydroxide ions; An anion exchange membrane exhibiting an ionic conductivity of at least 150 mS / cm at 80°C.
11. 11. The membrane of claim 10 in the form of a tubular composite, a hollow fiber, a dense flat film sheet or a thin film composite.
12. 11. The membrane of claim 10 having an ion exchange capacity of at least 3 meq / g in an alkaline aqueous medium at a temperature of from about 20° C. to about 100° C. for a minimum of 800 hours.
13. 11. An electrochemical device comprising the film of claim 10.
14. A fuel cell comprising the membrane of claim 10.
15. The random copolymer comprising one or more first repeat units of formula (IA) derived from a monomer of formula (I) and one or more second repeat units of formula (IIA) derived from a monomer of formula (II) is a copolymer comprising one first repeat unit of formula (IA) derived from a monomer of formula (I) and one second repeat unit of formula (IIA) derived from a monomer of formula (II). The membrane of claim 10.
16. The random copolymer comprising one or more first repeat units of formula (IA) derived from a monomer of formula (I) and one or more second repeat units of formula (IIA) derived from a monomer of formula (II) is a terpolymer comprising two different first repeat units of formula (IA) derived from two different monomers of formula (I) and one second repeat unit of formula (IIA) derived from a monomer of formula (II). The membrane of claim 10.
17. A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), norbornene (NB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-ethylbicyclo[2.2.1]hept-2-ene (EtNB) as the monomer of formula (II), and NR 5 R 6 R 7 being N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB) as the monomer of formula (II), and NR 5 R 6 R 7 being N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); A crosslinked polymer formed from 5-(4-bromobutyl)bicyclo[2.2.1]hept-2-ene (NBBuBr) as the monomer of formula (I), 5-hexylbicyclo[2.2.1]hept-2-ene (HexNB) as the monomer of formula (II), and NR 5 R 6 R 7 being N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA); and A crosslinked polymer formed from 5-(4-bromopropyl)bicyclo[2.2.1]hept-2-ene (NBPrBr) as the monomer of formula (I), 5-butylbicyclo[2.2.1]hept-2-ene (BuNB) as the monomer of formula (II), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA) as the NR 5 R 6 R 7 ; 11. The membrane of claim 10, comprising the crosslinked polymer selected from the group consisting of:
18. a) one or more first repeat units of formula (IA) derived from a monomer of formula (I); 【Chemistry 13】 (where: 【Chemistry 14】 represents the position of bonding to another repeat unit; Y and Y' are the same or different and are each independently selected from the group consisting of -CH 2 -, -CH 2 -CH 2 -, and -O-; m is an integer from 0 to 3; At least one of R 1 , R 2 , R 3 and R 4 is a group represented by the formula R-X; wherein R is selected from the group consisting of (C 1 -C 10 ) alkylene, (C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene(C 3 -C 8 ) cycloalkylene, (C 1 -C 10 ) alkylene(C 3 -C 8 ) cycloalkylene(C 1 -C 10 ) alkylene, (C 1 -C 10 ) alkylene(C 6 -C 10 ) arylene, and (C 1 -C 10 ) alkylene(C 6 -C 10 ) arylene(C 1 -C 10 ) alkylene; X is bromine; the remaining R 1 , R 2 , R 3 , and R 4 are each independently selected from the group consisting of hydrogen, straight or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; and One or more second repeat units of formula (IIA) derived from a monomer of formula (II): 【Chemistry 15】 (where: 【Chemistry 16】 represents the position of bonding to another repeat unit; Z and Z' are the same or different and are each independently selected from the group consisting of -CH 2 -, -CH 2 -CH 2 -, and -O-; n is an integer from 0 to 3; R 8 , R 9 , R 10 , and R 11 are the same or different and are each independently selected from the group consisting of hydrogen, straight or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; and NR 5 R 6 R 7 ; b) The film is NR in the presence of a base. 5 R 6 R 7 reacting with, where R 5 , R 6 , and R 7 At least one of (C 1 -C 10 ) alkylene N(R 5’ ) (R 6’ ), (C 3 -C 8 ) Cycloalkylene N(R 5’ ) (R 6’ ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) Cycloalkylene N(R 5’ ) (R 6’ ), (C 1 -C 10 ) alkylene (C 3 -C 8 ) Cycloalkylene (C 1 -C 10 ) alkylene N(R 5’ ) (R 6’ ), (C 1 -C 10 ) alkylene (C 6 -C 10 ) arylene N(R 5’ ) (R 6’ ), and (C 1 -C 10 ) alkylene (C 6 -C 10 ) Arylene (C 1 -C 10 ) alkylene N(R 5’ ) (R 6’ ) selected from the group consisting of; R 5’ and R 6’ are the same or different, and are linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; The remaining R 5 , R 6 , and R 7 are the same or different, and are linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; and c) The film obtained in b) is reacted with a compound of the formula NR 5’ R 6’ R 7’ with a tertiary amine of 5’ , R 6’ , and R 7’ are the same or different, and are linear or branched (C 1 -C 10 ) alkyl, (C 3 -C 8 ) cycloalkyl, (C 1 -C 10 ) alkyl(C 3 -C 8 ) cycloalkyl, and (C 1 -C 10 ) alkyl(C 6 -C 10 ) aryl; 11. A method of forming the film of claim 10, comprising:
19. 20. The method of claim 18, wherein the base is an alkaline base.
Citation Information
Patent Citations
Norbornene-type polymer having a quaternary ammonium functional group
JP2013513705A
Anion-exchange membranes and methods of making and using the same
WO2019191225A1